The Sustainable Developments Goals and Buddha’s Teachings - Dhakhwa, Sabita (Historical Journal, 2020)
The Sustainable Development Goals (SDGs), also known as the Global Goals, were adopted by all United Nations Member States in 2015 as a universal call to action to end poverty, protect the planet and ensure that all people enjoy peace and prosperity by 2030. The Buddha delivered several Dhamma discourses to diverse people in the various places for forty-five years; from the time he attained enlightenment until he entered into Mahaparinibbāna. These Dhamma discourses are related to non-violence, equality and peace. The elimination of all forms of gender based violence and promotion of equality are very much related with change of attitude and positive mind development. Moral conducts (Sila), Right speech, Right livelihood, Right understanding, practicing of loving kindness (Mettā, Saraniya Dhammas, etc are some of the Buddha’s teachings which can contribute to attitude change and positive mind development. The teachings of the Buddha are in harmony with the spirit of Gender equality goal of SDGs. Therefore, the article intends to throw light on the following aspects: What are the Buddha’s teaching for Gender equality? and how Buddha’s teachings can contribute to eliminate gender based violence and promote Gender equality which is one of the goal of SDGs.